HOW TO BE A UX/UI DESIGNER? - Tiawan Tiawan; Noor Syam Azwar; Amar Fauzi; Annisa Zachry; Vira Virginia (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The Covid-19 pandemic era is not a limitation in sharing knowledge with the public, Indorama Engineering polytechnic in collaboration with Bisa Ai has created a webinar, "How to be a UI/UX designer?" becoming a system designer in the era of society 5.0 can provide benefits in the form of measurable values, can be used as material to become an entrepreneur or work in a company with a position as UI/UX that designs applications so the application can be used properly by users. This community service introduces that the profession as a UI/UX design is also very promising, in this service the introduction of what UI/UX is, the tools used, the job and business prospects that can be generated, and the community in UI/UX. This service is also broadcast live using youtube media so that anyone who participates can play it back and hopefully it will be useful for all.